Impact of early developmental fluoride exposure on the peripheral pain sensitivity in mice. Issue 47 (30th September 2015) - Ma, Jing; Liu, Fei; Liu, Peng; Dong, Ying‐Ying; Chu, Zheng; Hou, Tie‐Zhou; Dang, Yong‐Hui
Abstract: Consumption of high concentration of fluoride in the drinking water would cause the fluorosis and chronic pain. Similar pain syndrome appeared in the patients in fluoride therapy of osteoporotic. The aim of the current study was to examine whether exposing immature mice to fluoride would modify the peripheral pain sensitivity or even cause a pain syndrome. We gave developmental fluoride exposure to mice in different concentration (0 mg/L, 50 mg/L and 100 mg/L) and evaluated their basal pain threshold. Von Frey hair test, hot plate test and formalin test were conducted to examine the mechanical, thermal nociceptive threshold and inflammatory pain, respectively. In addition, the expression of hippocampal brain‐derived neurotrophic factor (BDNF) was also evaluated by Western blotting. Hyperalgesia in fluoride exposure mice was exhibited in the Von Frey hair test, hot plate test and formalin test. Meanwhile, the expression of BDNF was significantly higher than that of control group. The results suggest that early developmental fluoride exposure may lower the basal pain threshold and be associated with the increasing of BDNF expression in hippocampus.